Quality of Quail Eggs (Coturnix joturnix japonica L.) After 15 Days Preservation Using Rambutan Leaves (Naphelium lappaceum L.) - Febiola, Cantika Riski; Atifah, Yusni (Department of Biology, Faculty of Mathematics and Natural Sciences, Universitas Negeri Padang, 2023)
Eggs are one of the foodstuffs that are easily damaged, if left in the open air (room temperature) the eggs only last 10-14 days, so it is necessary to apply a method to extend the durability of the eggs during storage, in this study the preservation by utilizing natural ingredients, namely rambutan leaves (Naphelim Lappaceum L.) The aims of this study was to determine the effect of rambutan leaf extract on the storage time of quail egg (Coturnix coturnix japonica L.). This study was an experimental study using a completely randomized design (CRD) with 10 treatments and 3 replications. The results of the study were analyzed using the ANOVA test and if it had a significant effect (P<0.05), continue with the DMRT. The results of the research showed that the best treatment for egg weight was 30% concentration and 24 hours of soaking time (A2B1), 45% concentration with 29 hours of soaking time (A3B2) for HU values, 15% concentration and 34 hours of soaking time (A1B3) for IKT, and the setting had no significant effect on the pH value and IPT value.